PENTINGNYA KETERLIBATAN ORANG TUA DI LEMBAGA PAUD DALAM MENSTIMULASI PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Evi Desmariani; Muzayyanah Muzayyanah; Jendriadi Jendriadi; Widdya Rahmalina (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
There are still many parents who take their children to go to kindergarten institutions with the aim that their children can learn to read, write, count and be good at (reading) the Koran. Like what happened in Hauriyah Halum Integrated Kindergarten. Since the learning process is implemented, parents only fulfill all the needs of the children requested by the institution for the learning process including completing school administration. After that, the parents are only tasked with taking the child to school in the morning and picking up the child from school after the learning process, and sometimes asking how many stars the child's work got. Parents do not think at all about the child's behavior while at school, such as annoying friends, making noise during the learning process, hitting friends, and saying bad words to friends. This is often conveyed by the teacher every time the child comes home from school with the hope that the parents advise the child while at home. However, every day there is no visible change and even more protracted. For this reason, it is necessary to do counseling on the importance of parental involvement in kindergarten institutions in stimulating children's socio-emotional development from an early age. Therefore, it is necessary to carry out community service in the form of counseling. The extension method is in the form of lectures and questions and answers. This community service aims to ensure that teachers always involve parents in educating children, especially in stimulating children's social-emotional development from an early age. So that children can follow the learning process and behave well to teachers and friends while they are at school. As a result of this community service, it is hoped that all parents can train themselves or get used to behaving well in front of children at all times while at home as teachers have been accustomed to while the child is in school.